1998
DOI: 10.1542/peds.101.2.e8
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Environmental Tobacco Smoke Exposure on the Respiratory Health of Children 2 Months Through 5 Years of Age in the United States: Third National Health and Nutrition Examination Survey, 1988 to 1994

Abstract: ABSTRACT. Objective. To measure the effect of environmental tobacco smoke (ETS) on respiratory health in a national sample of young children.Methods. The study evaluated children 2 months through 5 years of age participating in the Third National Health and Nutrition Examination Survey, 1988 to 1994. The group was a representative sample of the US population (N ‫؍‬ 7680). A parental report of household smoking or maternal smoking during pregnancy ascertained ETS exposure. Respiratory outcomes were based on par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
196
1
12

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(216 citation statements)
references
References 33 publications
7
196
1
12
Order By: Relevance
“…8,9,[11][12][13][14]20 In contrast, we found no association of exposure to environmental tobacco smoke with asthma in older children and adolescents. We did not, however, have a measure of maternal smoking-the most consistent marker for the adverse effects of exposure to environmental tobacco smoke.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…8,9,[11][12][13][14]20 In contrast, we found no association of exposure to environmental tobacco smoke with asthma in older children and adolescents. We did not, however, have a measure of maternal smoking-the most consistent marker for the adverse effects of exposure to environmental tobacco smoke.…”
Section: Discussionmentioning
confidence: 66%
“…We did not, however, have a measure of maternal smoking-the most consistent marker for the adverse effects of exposure to environmental tobacco smoke. 5,9,11,14 Instead, we relied on serum cotinine levels and reported smoking for any adult in the household. Thus, these differences may either represent problems with the measurement of exposure to environmental tobacco smoke or a lack of any association of environmental tobacco smoke and asthma in older children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, there are two odds ratios of interest: (1) the relative change in the odds of asthma comparing an individual in the medium category to an individual in the low category and (2) the relative change in the odds of asthma comparing an individual in the high category to an individual in the low category. Confounders/precision variables based on published literature were gender, parental asthma, presence of a household smoker, and income (Gergen et al, 1998;Jaakkola et al, 2001). For the first set of analyses (without interaction terms) we considered two sets of models: an unadjusted model using traffic exposure alone and an adjusted model that includes the additional confounder and precision variables outlined above.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that SHS was associated with asthma exacerbations or bronchial hyperactivity in older children, whereas others did not. 3,6,7,43,44 The vast majority of studies relied on parents' reports of smoking behavior to quantify the risk of asthma, wheezing, or diminished pulmonary functions associated with SHS exposure; fewer studies used objective biomarkers such as cotinine levels. 7,43,44 Although we found a significant reduction in the number of unscheduled asthma visits among children, there was not a corresponding reduction in the gaseous phase of tobacco smoke, as assessed with objective measures of air nicotine levels and biomarkers of internal doses.…”
Section: Discussionmentioning
confidence: 99%